From the Arthouse to the Grindhouse: Highbrow and Lowbrow Transgression in Cinema's First Century - Cline, John; Weiner, Robert G. (Rowman & Littlefield Publishers, 2010)
While there are numerous books on art and exploitation cinema, very few attempt to examine both. Covering the first 100 years of cinematic transgressions, From the Arthouse to the Grindhouse is a collection of numerous essays representing key contributions to overlooked, forgotten, or under-analyzed parts of film history. From cult favorites like Arch Hall Jr. to revered but under-documented marquee names like Lon Chaney, filmmakers both major and minor are covered here. Starting with a section that pairs exploitation pioneers like Dwain Esper alongside cutting edge auteurs like Erich Von Stroheim, the volume documents the bleeding edge of the high/low cultural divide. Other essays examine the sexual melodramas of Weimer German cinema, explore the concept of Borat as a model for the new standardized cult film, and discuss the films of directors Tod Browning, Pier Pasolini, and Peter Watkins. This volume also contains a section devoted to the idea of "reality" inside and outside the documentary sphere, emphasizing audiences' desire to believe that "this is really happening," whether they're horrified or titillated. Addressing many aspects of "transgression" in cinema, these essays suggest that the distance between the venues and the audiences may not be quite as wide as viewers might imagine.